The prognostic role of troponin I elevation after elective percutaneous coronary intervention. Issue 3 (March 2015) - Auguadro, Carla; Scalise, Filippo; Manfredi, Mariella; Casali, Valentina; Novelli, Eugenio; Specchia, Giuseppe
Abstract : Objectives: To assess the prognostic role of isolated troponin I (TnI) elevation after elective percutaneous coronary intervention (PCI) in patients with stable coronary artery disease. Background: The prognostic role of minor troponin elevation after PCI is controversial. Methods: A total of 1532 consecutive patients who underwent elective PCI were included. Follow-up data were obtained for 1432 of 1532 (93.4%) patients. The events taken into account in the follow-up included total mortality, cardiac death, hospitalization for acute myocardial infarction and/or unstable angina. Results: The following variables were identified as predictive of major adverse cardiac events (MACE) by univariate analysis: age 75 years at least ( P  = 0.012), ejection fraction less than 50% ( P  = 0.001), prior myocardial infarction ( P  = 0.031) and TnI 1.0 ng/ml at least after PCI ( P  = 0.04). The Cox-regression model identified the TnI elevation after PCI, the older age and the ejection fraction as independent predictors of MACE during follow-up (TnI: P  = 0.042; older age: P  = 0.001; ejection fraction: P  = 0.003). In a subgroup of patients with preserved ejection fraction, the incidence of MACE was significantly higher in those with TnI of at least 1.0 ng/ml at least than in the ones with TnI less than 1.0 ng/ml, with the highest incidence among the older cohort. The multivariate analysis confirmed the TnI elevation 1.0 ng/ml at least after PCI and the older age as predictors of MACE. Conclusion: This study documented that in clinically stable patients, minor TnI elevations after elective PCI are independent predictors of MACE during follow-up, as are older age and reduced ejection fraction. Additionally, TnI elevation was a predictor of MACE during follow-up in a subset of patients with preserved ejection fraction. The combination of TnI elevation and older age confers the highest risk of MACE.